A study to investigate the relationship between transcranial magnetic stimulation on cognitive impairment and neurotrophic factor in post-stroke patients - Li, Wenyan; Wen, Yinghua; Li, Wei; Liu, Jingjing; Liu, Sha; Wu, Junying; Gao, Yao; Xu, Yong (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to investigate the efficacy of transcranial magnetic stimulation on post-stroke patients in terms of cognitive impairment, and to observe its relationship with peripheral blood neurotrophic factor concentration and changes in brain area function.MethodsSixty patients with cognitive impairment after ischemic stroke were randomly assigned to group A (n = 30) and group B (n = 30) to receive TMS and sham stimulation of the left dorsolateral prefrontal cortex, respectively. The frequency of magnetic stimulation intensity in the TMS group was 10 Hz, and 10 stimulations were applied in the left DLPFC. Montreal Cognitive Assessment (MoCA), Digital Breadth Test (DST) and N-Back reaction times as well as determination of peripheral blood BDNF, NGF concentrations were assessed before and 2 weeks after stimulation, respectively, and the functional connectivity of each brain region in the assessment task state was analyzed using near infrared spectroscopy (fNIRS). Finally, a correlation study between peripheral neurotrophic factors and brain regions and in relation to cognitive scales was performed.ResultsAfter stimulation, patients in the TMS group had increased MoCA (p = 0.026), DST (p = 0.008) and N-Back (p = 0.007) scores compared to the sham stimulation group, as well as increased peripheral blood BDNF (t = 2.448, p = 0.021) and NGF (t = 2.885, p = 0.007) concentrations. The Pearson’s correlation interaction effect was significant between the patients’ left DLPFC brain region and the right DLPFC brain region (r = 0.492, p = 0.038). BDNF was negatively correlated with the N-Back (r = −0.4668, p = 0.038), NGF was significantly negatively correlated with the N-Back (r = −0.5692, p = 0.0019), and the rDLPFC brain region was positively correlated with the N -Back reaction times was positively correlated (r = −0.6516, p = 0.0243), and LDLPFC brain region was positively correlated with N-Back (r = −0.5012, p = 0.0244).ConclusionTMS improves cognitive function in post-stroke patients, changes in brain-derived neurotrophic factor concentrations under the influence of TMS, and also enhances connectivity in the bilateral DLPFC brain area network.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=216761.